Building Sustainability of Food Sovereignty in Lembata Regency through the MBKP Program: Cultural Approach and Field Study - Ananta, Daffa Adli; Fadil, Cholid; Imaningsih, Niniek (Pascasarjana Universitas Mataram, 2025)
This service activity aims to improve food sustainability in Merdeka Village through the integration of scientific and cultural approaches. The program identifies and leverages local resources, such as cassava, corn, and coconut, to develop innovative products that address societal challenges, including the lack of utilization of organic waste, limited access to simple technology, and a lack of product diversification. Four prototypes were successfully developed, namely shredded coconut pulp, cookies made from cassava flour and titi corn, caramelized cassava cakes, and organic fertilizer from livestock waste. The demonstration and training involved active community participation with significant results: 100% of participants succeeded in producing shredded coconut pulp independently, 90% of participants succeeded in making ready-to-sell cookies, and 80% of farmers showed understanding and skills in making organic fertilizer. This program has succeeded in optimizing local resources, reducing waste, and empowering communities to produce products that are sustainable, nutritious, and have high economic value. This activity shows the importance of integrating local cultural knowledge with technological innovation to achieve food sovereignty. This initiative not only answers the needs of the community directly but also provides a replicable model to promote sustainable agricultural practices and improve local economies in similar regions.